Clinical and Radiologic Spectrum of Odontogenic Keratocyst: Descriptive Study - Naveed Khan, Abdur Rehman, Alamgir, Zainab Jadoon, Shagufta Naeem, Shabana Naz (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Odontogenic keratocyst is relatively common developmental odontogenic lesion occurring with a frequency of approximately 10-14% of all jaw cyst. Aim: To find the clinic-radiologic pattern of odontogenic keratocyst cases. Study design: Descriptive cross sectional. Methodology: Present study was conducted at Pathology and diagnostic Medicine, Khyber Medical University Peshawar in which 83 patients were enrolled. An OPG x-ray was done for all the patients to see the nature of the lesion. Surgical specimens were stored in formalin solution. After gross examination, they were evaluated histopathologically for diagnosis of Odontogenic keratocyst according to WHO criteria2. Data was collected through performa by non-probability convenient sampling following ethical approval. Data was evaluated by using SPSS version 23. Quantitative data was presented as mean ± SD. Categorical data was presented by frequency and percentage. Chi square was applied with p-value <0.05 as significant. Results: Almost 55.4% were male patients. Almost 45.8% patients were in the 4th decade of their life. The mandible was the most common site of involvement accounting for 68.7%. An impacted tooth was associated in 26.5% of cases. Conclusion: It was concluded that OKC involved mandible while occurring in 4th decade of life among males commonly. There was an association with an impacted tooth, therefore to rule out the presence of odontogenic keratocyst, all impacted teeth should be assessed. Key words: Impacted Tooth, Multilocular, Odontogenic Keratocyst and Satellite Cyst.